Halal Food Production and Nutritional Value: A Study of MSMEs in Northern Nigeria - Adamu Abubakar Muhammad; Nabeela Usman El-Nafaty; Adam Muhammad Ardo; Rabi Shehu Dalhatu; Abubakar Aliyu Yakub (UIN Siber Syekh Nurjati Cirebon, 2025)
Introduction: The rapid growth of micro, small, and medium enterprises (MSMEs) in Northern Nigeria has coincided with an increase in consumer demand for halal–tayyib food products that meet both Islamic dietary requirements and nutritional criteria. This study explores the practices of halal food–producing MSMEs in Kaduna and Kano states, evaluating how they achieve compliance with Shariʿah criteria while delivering nutritionally balanced offers. For cultural, religious, and health reasons, the largely Muslim populace of northern Nigeria depends significantly on halal-certified goods. However, there is a dearth of empirical studies on how local MSMEs simultaneously manage certification, ingredient procurement, processing, and nutritional adequacy. While halal certification addresses ritual purity, it does not guarantee nutritional quality. Anecdotal evidence suggests that many small producers prioritize certification over nutrient profiling, which may potentially jeopardize public health. This study fills the gap by evaluating both halal compliance and nutritional value in the outputs of MSMEs. Methods: Using a mixed methods approach, 20 halal certified MSMEs were surveyed on their sourcing, processing, and quality control practices; 40 food samples (such as meat products, dairy, and baked goods) were analyzed in a lab to measure macro and micronutrient content; 20 in-depth interviews with MSME owners, halal certifiers, and nutrition experts provided contextual insights; quantitative data were analyzed using descriptive statistics and correlation tests; qualitative data were subjected to thematic analysis. Results: Only 40% of the sampled MSMEs met national standards for essential nutrients (protein, iron, and vitamin A), despite the fact that 90% of them maintained valid halal certification. Common obstacles to nutritional quality included gaps in regulatory oversight, limited technical capacity, and cost constraints on fortified ingredients. MSME owners expressed a strong commitment to halal integrity but lacked knowledge about nutritional guidelines. The study emphasizes the need for integrated halal–nutritional frameworks and capacity-building initiatives aimed at MSMEs. Policymakers and Islamic authorities can collaborate to develop training modules and offer incentives for nutrient enrichment, in addition to halal certification. Conclusion and Suggestion: Ensuring both halal compliance and nutritional adequacy is crucial for maintaining public health and fostering consumer trust. In Northern Nigeria, enhanced collaboration among certification organizations, nutrition organizations, and MSMEs can foster a halal food industry that is both ethically sound and health-promoting.